MOTIVASI SOSIAL DALAM RITUS TAREKAT - Djuhan, Muhammad Widda (ASANKA : Journal of Social Science and Education, 2020)
The phenomenon of the tarekat in Javanese society, especially since the arrival of the spreaders of Islam until now, is firmly rooted among Muslims. Although there are criticisms that suspect that such practices can tarnish monotheism, in fact the activities of the tarekat never fade at all even more and more people tend to follow the tarekat activities where they live especially after there are many problems in people's lives. The field research, which took the object of special rituals in the qariahyah wa naqshabandiyah tarekat in the mojoroto Gelanglor sukorejo mosque, Ponorogo district, highlighted social motivations in the selasan rituals which were followed by selasan followers. In fact, many people who live around the mosque take part in the activities of the congregation qodiriyah wan naqshobandiyah. Nevertheless, their participation motivation is not singular because it is very dependent on the mindset, religious understanding and traditions that surround it. This study came to the conclusion that there was motivation [1] Improving the deeds of worship in the afterlife, [2] Looking for spiritual peace with the routine of worship activities held [3] Resolving the problems of their lives with the help of the spirit of the murshid. These various motivations show that we cannot make unilateral claims to the tarekat followers, especially the qodiriyah wa naqshabandiyah tarekat.